In silico analysis on inhibitory potentials of derived peptides from human breast milk against SARS-CoV-2 infection - Villapaz, Rogel L (Animo Repository, 2021)
Novel therapeutic drug discovery against the severe acute respiratory syndrome-corona virus-2 (SARS-CoV-2) focuses on in silico analysis of potential medicines that inhibit the viral entry, proteases, and replication. Human breast milk contains compounds, bioactive peptides, essential for the growth, nutrition, and protection of children. In the present study, six known bioactive peptides derived from human breast milk were analyzed in silico for their potential inhibitory activity on angiotensin-converting enzyme 2 (ACE2), dipeptidyl peptidase 4 (DPP4), and SARS-CoV-2 spike protein. These peptides were found to have significant inhibitory activity and are non-toxic. The active amino acids within these peptides that interact with ACE2 and DPP4 were also identified. Molecular docking shows that all six peptides may exhibit non-competitive inhibition in which it binds to other sites of the protein which may induce conformational changes and prevent viral attachment. The docking scores revealed that the binding affinities of these peptides to ACE2, DPP4, and SARS-CoV-2 spike protein are stronger than SARS-CoV-2 spike protein to ACE2 and DPP4. Among these six peptides, IYPSFQPQPLI is found to be the best inhibitor for ACE2, DPP4, and SARS-CoV-2 spike protein. These peptides are potential drug candidates for coronavirus disease-2019 (COVID-19) treatment, however, in vitro and in vivo studies must be conducted to ensure efficacy and safety.